A non-invasive methodology for ATAA rupture risk estimation. (3rd January 2018) - Trabelsi, O.; Gutierrez, M.; Farzaneh, S.; Duprey, A.; Avril, S.
Abstract: Ascending thoracic aortic aneurysms (ATAA) are a life-threatening pathology provoking an irreversible dilation with a high associated risk of aortic rupture or dissection and death of the patient. Rupture or dissection of ATAAs remains unpredictable and has been documented to occur at diameters less than 4.5 cm for nearly 60% of patients. Other factors than the aneurysm diameter may highly affect the predisposition to rupture. In order to have a better insight in rupture risk prediction, a bulge inflation bench was developed to test ATAAs samples collected on patients during surgical interventions. Preoperative dynamic CT scans on a cohort of 13 patients were analyzed to estimate volumetric and cross-sectional distensibility. A failure criteria based on in vitro ultimate stretch showed a significant correlation with the aortic membrane stiffness deduced from in vivo distensibility. These results reinforce the significance of stretch-based rupture criteria and their possible non-invasive prediction in clinical practice.